Memahami Pendidikan Islam - Subhan, Fauti (Nadwa, 2013)
This article discusses the relationship between Islamic education and various elements of life. The linkage between the theoretical side of Islamic education and the practical side of Islamic education is also presented here. In the study, the theoretical and applied dimensions of Islamic education can be discussed separately, but in practice, these two dimensions are inseparable. In principle, the Islamic education issues cannot be separated from any variety of issues. The Islamic education is always associated with the various elements of life, es-pecially human beings. Human beings can grow and develop properly with Is-lamic education. Conversely, humans (Muslim) also become actors for the de-velopment and the decline of Islamic education. The relationship between Mus-lims and Islamic education just likes a piece of money, which is composed of two different sides, but inseparable one another. In Islamic societies, education be-comes a key of progress.